Cross-Border Mergers and acquisitions: Financial and institutional forces - Nicolas Coeurdacier; Roberto A. De Santis; Antonin Aviat (European Central Bank (ECB), 2009)
Cross-border mergers and acquisitions (M&As) sharply increased over the last two decades. It is often pointed out that cross-border capital reallocation is partly the result of financial liberalization policies, government policies and regional agreements. In this paper, we identify some of the main forces driving cross-border M&As using a unique database on bilateral cross-border M&As at the sectoral level (in manufacturing and services) over the period 1985-2004. We focus on the role of institutional and financial developments with a special attention to the role played by the European Integration process. We identify the impact of (i) joining the European Union and (ii) joining the Euro on cross-border M&As. We show that EU and EMU have almost doubled M&As in manufacturing towards their members from all over the globe, with an additional 50% increase within EMU countries. Conversely, the service sector did not exploit the opportunity offered by the single currency. We also show how cross-border M&As are linked to the acquirer expected profitability and provide insights on the effectiveness of policies to attract foreign capital (such as corporate tax incentives, and interventions to improve the country's financial system and product market regulations).
Keywords: F30; F36; F41; G11; 330; Cross Mergers and Acquisitions; Euro; Gravity Equation; Fusion; Übernahme; Multinationales Unternehmen; Eurozone; Euro; Gravitationsmodell; EU-Staaten